MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK DENGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA WORDWALL PADA MATA PELAJARAN MATEMATIKA KELAS VI SD NEGERI 060857 MEDAN TEMBUNG - Satrina Sihite; Mandra Saragih; Lidya Roida Sihombing (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to increase students' learning motivation by using a Problem Based Learning (PBL) learning model assisted by Wordwall Media in Mathematics Subject Class VI SD Negeri 060857 Medan Tembung. The type of research used is Classroom Action Research (PTK) which consists of four steps: planning, implementation, observation, and reflection. This research was carried out collaboratively with classroom teachers and peers. The subjects of the study were 24 students in class VI. The methods used are observation and questionnaires, with qualitative descriptive data analysis techniques. The data collected and organized are then described based on the researcher's views and the support of relevant theories. Observation was carried out for 3 cycles, and the results showed an increase in students' learning motivation: 63% in cycle 1, 73% in cycle 2, 82.1% in cycle. This study shows that the application of the PBL model with the help of wordwall interactive media has a significant impact on increasing the learning motivation of grade VI students, especially in mathematics subjects.